Negotiating development : rationales and practice for development obligations and planning gain - Healey, Patsy (E & FN Spon, 1995)
Planning gain is the legal process by which property development is linked to social provisions. This book examines the rationale for planning gain and development obligations and reviews the practice of development negotiation through a wide range of case histories.